An Evaluation of Treatment Time and Intrafraction Motion in Stereotactic Body Radiation Therapy - Leila Rough; Julie Burbery; Catriona Hargrave; Elizabeth Brown (Journal of Medical Radiation Sciences)
ABSTRACT Introduction Image guided‐radiation therapy (IGRT) protocols are adopted to ensure the accurate dose delivery of patient treatments. This is especially important in hypofractionated treatments, such as stereotactic body radiation therapy (SBRT), as high doses of radiation are delivered, and incorrect treatment can have a significant impact on tumour control and toxicity. This study aimed to establish mean treatment times from the localisation image to the post‐treatment image in SBRT liver, lung and spine patients that utilised Elekta Intrafraction Imaging (IFI). The magnitude of intrafraction motion exhibited as time elapses during the treatment fraction was also determined. Methods IGRT data for 20 SBRT patients was retrospectively collected, including imaging times and shifts made from each pre‐, during and post‐treatment cone‐beam computed tomography (CBCT) scan. Total treatment fraction time, time between each image acquired and the 3D vector of the shifts were calculated. Descriptive statistical analysis was performed. Results The IGRT data associated with 332 CBCT images was evaluated. The average treatment time was longest in the liver (19.3 min), followed by lung (14.9 min) and spine (14.2 min). Liver patients had a mean shift 3D vector (0.1 cm), with 7.8% of shifts > 0.3 cm. Lung patients had a mean vector of 0.1 cm with 3.8% > 0.3 cm, and spine patients had a mean vector of 0 cm with 0% > 0.2 cm. Vectors > 0.3 cm occurred at multiple imaging timepoints (range: 4.9–24.4 min) for liver and lung patients. Conclusion Intrafraction imaging is required in liver and lung SBRT treatments to identify instances where clinical tolerances are exceeded.